Identification of Screw Press Machine Damage Using Failure Mode And Effect Analysis Method in PT. Socfinfo Seunagan - Sarbeni; Arie Saputra (Jurnal Inotera, 2023)
The palm oil mill (PKS) is a place that serves as a place to process fresh fruit bunches (FFB) of palm oil into crude palm oil (CPO), palm kernels (kernels), fiber and palm shells. The processing of palm fruit into palm oil is carried out using production machines, one of which is a Screw Press machine [1]. In a factory, there are usually problems, one of which is at the Screw Press engine station. The Screw Press machine is one of the most important machines in palm oil mills. This study aims to identify damage and failures that occur in screw press machines. This study uses the failure mode and effect analysis (FMEA) method, which is to find out or observe the level of failure and damage that occurs in the screw press machine so that it can minimize failures / damage that occur. Based on the results of the study, there were 9 failures and risks that occurred in the screw press machine components, with the highest Risk Priority Number found in the Special Bearing components with a value of While the lowest value is in the Spur Gear component, which is with a value of 24. From these results, it can be concluded that the Special Bearing component is a priority / priority for repairs.